Evaluating training and development in UK universities: staff perceptions. Issue 6 (1st July 2014) - Robson, Fiona; Mavin, Sharon
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to analyse individual experiences of learning evaluation in UK Higher Education Institutions (HEIs) and identify areas for improvement as part of an HEFCE LGM funded project. Design/methodology/approach – Eight focus groups were included in two universities with staff in similar roles. After transcription, the data were analysed using template analysis to identify and compare key themes from across both universities. Findings – The context of UK higher education is clearly important due to the diverse job roles and on-going sectoral changes. Three key themes emerged; first was a lack of clarity from the learners on learning evaluation. The second key theme centres on the format, method and timing of capturing evaluation data and the perception that a "one size fits all" approach is not appropriate. The third finding suggests that line managers do not currently fulfil their critical roles in the process. Research limitations/implications – Small number of research participants and a focus on two universities. In addition, participants were relying on their memories of past evaluation experiences. Practical implications – Ensuring learners understand reasons for evaluating their learning is important. HEIs should utilise a more diverse range of tools at the design stage to collect evaluation data. All stakeholder roles need to be clarified, and line managers require additional support. Originality/value – First, we address a gap in the existing sector-specific literature identified by Burgoyne et al. (2009) who contend that there is a lack of research in this area. Second, we contribute to the development of research in the journal by analysing evaluation from the perspective of the participants, and third, we offer recommendations for practice.